Modal Sosial dan Pembentukan Karakter Religius Siswa: Studi Kualitatif di Sekolah Menengah Pertama - Hidayah, Nurul; Hanif, Muh. (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the role of social capital in the formation of religious character in junior high school students. The research approach used is descriptive qualitative with data collection techniques in the form of non-participant observation, semi-structured interviews, and documentation. The research informants consisted of the vice principal for student affairs, the Islamic Religious Education teacher of grade VII BP, and ten students of grade VII B. Data were analyzed through the process of data reduction, data presentation, and drawing conclusions, with data validity tested through triangulation of sources and techniques. The results of the study indicate that social capital plays a role in the formation of religious character in students through three main dimensions. First, the social network between teachers, students, parents, and peers creates a system of mutual supervision and social support that strengthens the consistency of religious habits both at school and at home. Second, school social norms manifested through discipline, school culture, and religious habits function as pedagogical instruments that shape religious habits through the mechanism of internalization of values ​​and continuous habits. Third, trust between teachers and students creates a safe and supportive learning environment that facilitates the internalization of religious values ​​emotionally, not just cognitively. Thus, social capital plays a role in the formation of religious character of students at the junior high school level, through collaboration between schools and families, consistent application of norms, and building trust between teachers and students.